المقاربة الامريكية في الحرب على الارهاب - شرقي, محمود (revue mofakir; No 09 (2013): مجلـــة المفكــر, 2018)
After he was elected as a president of the United States of America in the first mandate, president Barack Obama declared in the first interview after elections with Alarabiya News Network that yes; war on “terror” was ended and conflict “with or against us” what called –long term war- in which “freedom loving” West face undefined darkness forces that includes everything starting form Al-Qaeda till Palestinian national struggle fighters under the name of “Islamic Fascism” had been stopped and the rest does not matter, “terrorist” organizations had been defeated and this is not a war but strategic challenge. Through the above, I ask the following questions: What is the strategy adopted during the administration of former President George Walker Bush in the fight against "terrorism" Do you know a shift in the era of the current administration of President Barack Obama? Whether we can say that the war on "terrorism" has effectively ended after the statements and commitments?